PUSAT PERAWATAN HOSPIS DENGAN PENDEKATAN ARSITEKTUR BIOFILIK DI KOTA PALANGKA RAYA - Putri, Suci Cahyani; Widati, Titiani; Syahrozi, Syahrozi (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2025)
The need for palliative care and hospice services in Indonesia continues to increase, but the availability of facilities remains limited due to a suboptimal referral system between healthcare services. Hospice, as part of palliative care, focuses on improving the quality of life of terminally ill patients through a holistic approach encompassing medical, emotional, social, psychological, and spiritual aspects. Based on the Peaceful End of Life theory, the creation of comfort, tranquility, and respect for patient dignity are the main principles in the treatment room. Therefore, a space that supports healing is needed, including through the relationship between humans and nature, which can be realized through a biophilic architectural approach. This study aims to design a hospice facility with a biophilic architectural approach, in order to create a healing environment connected to nature to support patient tranquility and comfort. The method used is descriptive qualitative through literature studies, comparative studies, precedent studies, site analysis, and the formulation of a design concept.